Penilaian Kondisi Bangunan Gedung Berdasarkan Metode Matriks Condition Survey Protocol (CSP1) Studi Kasus: PP Sunan Ampel Banyuwangi - Yuni Ulfiyati; Enes Ariyanto Sandi; Duta Agung Prayojana Fajrul Mahdi (Politeknik Negeri Lhokseumawe, 2025)
Â Abstract â€” The Sunan Ampel Islamic Boarding School building is a religious education facility that has been operating for 15 years. Routine maintenance has not been carried out on the building, resulting in a decline in quality. Over time, many factors can cause a decline in quality and damage the structure and architecture of the building. Therefore, to maintain the function and usability of the building, researchers need to assess the condition of the building. This study aims to determine the overall condition value of the building. In the process, data collection was carried out using the observation method while data processing used the Condition Survey Protocol 1 (CSP 1) Matrix method by adjusting the predetermined criteria. The results of this study can determine the condition value of the building at the Sunan Ampel Islamic Boarding School building. After data analysis, there were 359 damages in the Sunan Ampel Islamic Boarding School building. Of which 343 damages require planned maintenance, 10 damages require condition monitoring, and 1 damage requires serious attention. Based on the Condition Survey Protocol 1 (CSP 1) Matrix method, the overall building condition scored 1.25 (on a scale of 1-4), indicating the building is classified as good, meaning the structure remains strong and stable. Damage/defects are limited to the exterior.Keywords: Building Structure; CSP; Matriks; Condition Assesment